Outside the Circle: A Case Study ofVolunteer Activities of AdultsWith Low Literacy Skills - Donna Anderson; Allan Quigley (Adult Education Research Conference, 2007)
This study of volunteer activities among 21 adults with low literacy skills in a social assistance program in Nova Scotia revealed attitudes and motivations relating to volunteerism among program recipients, as well as the six employment support workers who counselled them. Findings indicated that the definitions and understandings of “volunteerism” do not include “informal” volunteerism and client’s non-traditional volunteerism was ultimately discouraged by the counsellors, leading clients to slowly disengage from their community over time.